An Investigation of Mediational Process in Social Learning During Online Language Learning - Sukimin, Ira Syaqira; Rahmat, Noor Hanim; Sim, Mok Soon; Arepin, Mazlen; Abidin, Nur Sherina Zainal; Haron, Haeza (International Journal of Asian Social Science, 2021)
Online learning has become a new trend in the world. To teach online effectively, the instructors have to improvise their course content. Learners have mixed feelings over online learning, some of them prefer the face-to-face teaching; but some are comfortable with the online teaching mode. Previously, the success of language teaching has always depended on face-to-face interaction. However, language is taught online now. Therefore, this study was carried out to investigate the mediational process in social learning during online language learning. 111 diploma, bachelor degree and postgraduate students had participated in this quantitative study in a public university in Malaysia. The instrument used is a questionnaire with 29 items. This study examines the influence of online language learning on learner-to-learner, learner-to-instructor, learner-to-content interaction and mediational process. The results show there is a significant difference in education level. Findings in this study reveals that support from peers plays a crucial role as it prevents students from dropping out of the course. The students prefer teaching style that involves their active participation. The findings also indicate that students find it is important to get an overview of the content before the class begins. Lastly, learning motivation increases when instructor gives good comments during online lessons. Learners also need to learn to be more responsible to make sure their online learning time is filled with successful learning and interactions.